Evaluasi Molekuler dan Lapangan terhadap Galur-galur Padi Berumur Genjah dan Produktivitas Tinggi Turunan Ciherang - Prasetiyono, Joko; Dadang, Ahmad; Ma’sumah, Ma’sumah; Tasliah, Tasliah; Fatimah, Fatimah; Silitonga, Tiur Sudiaty (Jurnal Penelitian Pertanian Tanaman Pangan, 2015)
Improving Ciherang rice variety for earliness and higher productivity was obtained using Marker Assisted Backcrossing (MAB). Among 78 lines of BC2F4 generation of Ciherang x Nipponbare were obtained from greenhouse and molekuler analysis selection. Field evaluations were conducted at two locations, namely field station of Sukamandi (Indonesian Center for Rice Research, West Java), and field station of Maros (Indonesian Cereals Research Institute, South Sulawesi). Molecular analysis was performed using markers RM1362 and RM7601 which are flanking markers for the QTL region for Hd2 gene, located on chromosome 7. Flowering time and grain yield were evaluated among BC2 F4 lines. Five lines flowered earlier and yielded higher than Ciherang were selected for background analysis using microsatellites covering the rice chromosomes. The earliest flowering line was BC2F4 CihNip-60 (at 74 days, 4 days earlier than that of Ciherang), and the highest yield (which flowered earlier than Ciherang) was BC2 F4 CihNip-23, namely (2.20 t/ha higher than Ciherang). A total of 74 (95%) BC2 F4 lines showed QTL region of Hd2 gene in homozygous condition. This showed that molecular selection from F1 generation of BC2 F4 was able to identify homozygous gens and almost free of contaminant plant. Genetic backgrounds of the five BC2 F2 selected lines were similar to that of Ciherang. Based on the agronomic and molecular marker, twenty five lines of BC2 F4 flowered earlier than did Ciherang and yielded higher than did Ciherang. These lines should be further evaluated for their stability